Balance and single line to ground fault location in electrical distribution system - Faradonbeh, M.A.; Mokhlis, Hazlie; Karimi, M.; Shahariari, A. (IEEE, 2011)
This paper outlines impedance based technique and its application for determining the location of a fault on a distribution system. A few well-know fault location methods are first discussed and analyzed to highlight its practicality as compared to impedance based technique. The practicality of the impedance based technique in locating a fault is shown by testing it on a Canadian distribution network. The algorithm of the impedance based technique is developed and integrated into PSCAD/EMTDC software by using C-interface and FORTRAN Language. Various test cases showed the practicality of the impedance based technique in locating a fault.